Renegotiating domestic violence: police attitudes and decisions concerning arrest - Myhill, Andy (Policing and society, 2019)
This paper presents findings from a comparative study of police decision-making. Interview data are used to revisit Hoyle’s [1998. Negotiating domestic violence: police, criminal justice and victims. Oxford: Oxford University Press] explanatory model of police decision-making in response to domestic violence. The analysis suggested Hoyle’s model remains relevant: officers were more likely to arrest if there was evidence of a criminal offence they perceived as serious (most often physical violence), and if they perceived ongoing risk of harm to the victim. The data did suggest official policies around presumptive arrest are now more salient, but that officers continue to use traditional ‘craft’ work to circumvent such policies in cases where they perceive the risk of further harm to be minimal. Implications for practice and debates around the efficacy of arrest are discussed.